Validation of A Measuring Scale of The Factors for The Employability of Millennials - María Teresa De la Garza Carranza; Jorge Armando López Lemus; Eugenio Guzmán Soria; Quetzalli Atlatenco Ibara (Gadjah Mada International Journal of Business, 2020)
Today the retention millennial workers is a challenge for organizations. The purpose of this paper is to propose ideas to the decision makers, to lessen the high rate of personnel turnover in all kinds of industries in many countries. This research validates an instrument thatevaluates the employability factors of millennials in Mexico, according to their own expectations. We based our study on the previous literature about the millennial generation in many countries. To validate the questionnaire, a sampling of 781 workers from the states of Querétaro and Guanajuato in México was conducted. The method used to achieve the objective was through exploratory and confirmatory factor analyses. The confirmatory factor analysis was conducted using structural equation modeling, and tested two different methods: first order and second order models. With the three methods, exploratory, first order and second order factor analyses, similar results were obtained. In the analysis of the statistical techniques, two latent variables associated with the expectations of this generational group were generated. The factors found are “personal satisfaction with the organization” and “satisfaction with the organization’s social commitment.” These two factors are supported by the literature of other researchers. It is suggested that this questionnaire be validated in other countries but also in other regions of Mexico, using different productive sectors, thereby obtaining a broader perspective that will allow us to understand not only what millennials want from their work, but to what extent they want it